ЎҚИШ, НУТҚИЙ ФАОЛИЯТНИНГ ИНСОН ТАФАККУРИНИ ШАКЛЛАНТИРИШДАГИ ЎРНИ - Атаев, Ш.А. (SCIENCE and SOCIETY, 2019)
The article is dedicated to the role of reading in the development of the human mind. The author gives characteristics of reading proposed by the majority of scientists. The illustrative material from the tragedy „Faust“ by Goethe has been used by the author.